2022
DOI: 10.1136/bmjopen-2022-062706
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to improve media coverage of medical research: a codesigned feasibility and acceptability study with Australian journalists

Abstract: ObjectivesAlthough the media can influence public perceptions and utilisation of healthcare, journalists generally receive no routine training in interpreting and reporting on medical research. Given growing evidence about the problems of medical overuse, the need for quality media reporting has become a greater priority. This study aimed to codesign and assess the feasibility of a multicomponent training intervention for journalists in Australia.DesignA small pragmatic feasibility study using a pre- and postd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Previous studies mainly focused on retrospective analysis of data [ 14 , 15 ] or on the analysis of treatment for a specific disease or the overuse of a single service [ 16 ] and the influence factors of medical overuse [ 17 , 18 ]; some findings sought to determine if there was variance among medical specialties [ 19 ]. To reduce medical overuse, it is found that intervention's impact on media coverage of medicine can help patients to stay away from medical overuse [ 20 ]. It is found that NHSA's supervising and punishment of doctors' behaviour, establishing reputation mechanism, and protecting patient's right are important factors to restrain medical overuse behaviour [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies mainly focused on retrospective analysis of data [ 14 , 15 ] or on the analysis of treatment for a specific disease or the overuse of a single service [ 16 ] and the influence factors of medical overuse [ 17 , 18 ]; some findings sought to determine if there was variance among medical specialties [ 19 ]. To reduce medical overuse, it is found that intervention's impact on media coverage of medicine can help patients to stay away from medical overuse [ 20 ]. It is found that NHSA's supervising and punishment of doctors' behaviour, establishing reputation mechanism, and protecting patient's right are important factors to restrain medical overuse behaviour [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In an experimental study on the impact of different formats of news coverage of an epidemic on risk perceptions of the public, Klemm et al found that perceptions of risk and severity were primarily driven by objective risk characteristics rather than emotion-laden news formats [ 10 ]. Journalists, therefore, can have a key role in presenting objective information about risk, yet often have no formal training in statistical reasoning [ 11 ] or presenting and interpreting medical research [ 12 ] and can rely on narratives rather than numbers [ 13 ].…”
Section: Introductionmentioning
confidence: 99%